1991
DOI: 10.1521/jaap.1.1991.19.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Developmental Transformations During the Various Phases of Motherhood

Abstract: The developmental processes that surround pregnancy and motherhood exert powerful and all-encompassing effects on the lives of the women undergoing such changes. Research has recently determined that the physiological and emotional transformations that occur in pregnant women may have a significant impact on the relationship that gradually develops between mothers and their infants. The growth of this relationship with the infant is directly related to the developmental challenges confronting the expectant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Further, our statistical controls may account for the fact that we did not replicate some previous findings and clinical impressions. On the other hand, since it has been suggested that by the end of pregnancy a woman has generally reached reconciliation with her internalized relationships, particularly those relating to her own mother (Raphael-Leff, 1991; Trad, 1991), it may be that issues relating to mental representations of other aspects of herself and her relationships have been processed in dreams at earlier stages of pregnancy. This possibility is consistent with our finding that dreams depicting the woman as a daughter and as part of her own family along with parents and family representations were not associated with morbid elements among pregnant women whereas they were among non-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our statistical controls may account for the fact that we did not replicate some previous findings and clinical impressions. On the other hand, since it has been suggested that by the end of pregnancy a woman has generally reached reconciliation with her internalized relationships, particularly those relating to her own mother (Raphael-Leff, 1991; Trad, 1991), it may be that issues relating to mental representations of other aspects of herself and her relationships have been processed in dreams at earlier stages of pregnancy. This possibility is consistent with our finding that dreams depicting the woman as a daughter and as part of her own family along with parents and family representations were not associated with morbid elements among pregnant women whereas they were among non-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation may be that sleep troubles are more likely to occur in the babies born to the mothers without previous experience in infant rearing and handling. It is also known that the first-time mothers are most likely to undergo such psychological and emotional changes that may affect not only her self-identity but also sense of self, character, and self-esteem [39,51], factors…”
Section: Discussionmentioning
confidence: 99%
“…Some women pointed out that they felt some ambivalence was "normal." When ambivalence was excessive and sustained, there was a tendency to displace the emotional concerns of pregnancy and motherhood onto the physical aspects of pregnancy and childbirth, such as the bodily changes and discomforts of pregnancy , 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 618 619 620 621 622 623 624 625 626 627 628 629 630 631 632 633 634 635 636 637 and the pain of labor, also noted by Trad (1991). Persons conducting assessments of pregnancy acceptance need to be cognizant of this type of displacement.…”
Section: Discussionmentioning
confidence: 99%
“…When resolution of psychosocial conflict occurred slowly or not at all, even a planned pregnancy was difficult to accept. If residual conflict still seemed unresolved by the third trimester, it was expressed more indirectly -for example, in dreams and in intense fears about labor, responses also reported by Trad (1991) and Cohen (1988). Examples of this are provided in the following sections.…”
Section: Planning and Wanting The Pregnancymentioning
confidence: 99%